A Case Report of Autoimmune Glial Fibrillary Acidic Protein Astrocytopathy Diagnosed After Long Term Diagnosis of Chronic Lymphocytic Inflammation With Pontine Perivascular Enhancement Responsive to Steroids - Yin, He-Xiang; Zhou, Yan; Xu, Yan; Li, Ming-Li; Zhang, Zhe; Zhou, Li-Xin; Zhang, Yao; Zhu, Yi-Cheng; Peng, Bin; Cui, Li-Ying (Frontiers in Neurology, 2020)
Cases of autoimmune glial fibrillary acidic protein (GFAP) astrocytopathy who were initially diagnosed with chronic lymphocytic inflammation with pontine perivascular enhancement responsive to steroids (CLIPPERS) were rarely reported. Herein, we reported a 31-year-old woman who presented with 7 years of recurrent headache. Her clinical history, symptoms, brain MRI enhancement features, and response to treatment during each attack were reviewed. Her brain MRI 7 years ago demonstrated characteristic pepper-like enhancement of pontine and cerebellum and her symptoms resolved completely after taking a high-dose of steroids. She was suspected with the diagnosis of CLIPPERS, and she experienced five relapses once the oral steroid was tapered below 20 mg/day. During her last relapse, she experienced fever and psychosis, and GFAPα-antibodies were detected in her serum and cerebrospinal fluid by antigen-transfected HEK293 cell-based assay (indirect immunofluorescence assay). She obtained relief again after steroid therapy, and her diagnosis converted to autoimmune GFAP astrocytopathy. Autoimmune GFAP astrocytopathy may mimic CLIPPERS, both clinically and radiologically. Long-term follow-up is essential for necessary diagnosis revision at each new attack in patients with a diagnosis of CLIPPERS.